Solar energy integration in off-grid communities: empowering remote areas in Bangladesh for sustainable development - Khusnur Jahan Shapna; Jianfeng Li; Md Lokman Hossain (Discover Sustainability)
Abstract Global energy demand rises with population and economic growth. In Bangladesh, the fossil fuel-dependent grid fails to reach coastal areas, so solar home systems (SHSs) provide viable off-grid electrification, though their usage and challenges remain understudied. In this study, we utilized a questionnaire survey at the household level, Focus Group Discussions (FGD), and Key Informant Interviews (KII) with stakeholders to assess the utilization of solar energy, examine the influence of SHS on households’ economic activities, and explore challenges in six coastal sub-districts in Bangladesh. Results reveal that 100% of households in the studied region rely on SHS for basic lighting, underscoring a universal need for this fundamental service. Access to electricity significantly enhanced social safety, disaster preparedness and living standard across the sub-districts. The utilization of solar energy had a positive influence on households' economic activities. Notably, 83% of SHS users reported an improvement in their economic well-being, leading to new ventures, including tailoring enterprises (58% of users), and poultry farming (42%). Adverse weather conditions (frequent foggy weather), negatively affected SHS performance, with 68–88% households reported. Concerns about environmental consequences were raised by 84% respondents in Cox’s Bazar and 21% respondents in Noakhali. To address the challenges, households employ various strategies including prioritizing essential appliances, reducing working hours at night, and using alternative energy sources to overcome these obstacles. The study findings provide practical insights for policymakers, firms, and NGOs involved in promoting green energy and SHS initiatives for underserved populations. By building partnerships between local governments, microfinance institutions, and community members, policies can be tailored to address barriers such as affordability and accessibility, ultimately promoting greater adoption of SHS and other renewable energy solutions.